Pemetaan Penelitian Terkait Keamanan Data di Indonesia - Yuadi, Imam; Khusniah, Lailatul (PETIR, 2022)
This research aims to be able to find out the tendency to use keywords in research related to data security in Indonesia. This study uses the method of bibliometric studies. The data was taken from a database published by Scopus in 2019 to 2021. Bibliometric data analyzed and visualized using VosViewer. Total research after the limit was generated 2,497 data globally and research related to security data in Indonesia found 31 studies in the form of journal articles. In Indonesia found 13 main keywords used in the study, namely Data Hiding, Data Protection, Data Security, Information Security, Reversible Data Hiding, Steganography, Cloud Computing, Cryptography, Network Security, Pixels, Security, and Security Of Data. Then after analysis was concluded that keyword Cryptography and Network Security are most often used in research related to data security globally and in Indonesia. ABSTRAK Penelitian ini bertujuan agar dapat mengetahui penelitian terkait Keamanan data di Indonesia. Penelitian ini menggunakan metode Studi bibliometrik. Data diambil dari database yang diterbitkan oleh Scopus dalam tahun 2019 hingga 2021. Data bibliometrik yang dianalisis dan divisualisasi menggunakan VosViewer. Hasilnya ditemukan Total penelitian setelah dilakukan limit dihasilkan 2.497 data secara global dan penelitian terkait data security di Indonesia ditemukan 31 penelitian berbentuk artikel jurnal. Di Indonesia ditemukan 13 keyword utama yang digunakan dalam penelitian yaitu Data Hiding, Data Protection, Data Security, Information Security, Reversible Data Hiding, Steganography, Cloud Computing, Cryptography, Network Security, Pixels, Security, Dan Security Of Data. Kemudian setelah dianalisis didapat kesimpulan bahwa keyword Cryptography dan Network Security paling sering digunakan dalam penelitian terkait keamanan data secara global dan di Indonesia.